Barriers and Enablers of indigenous Child protection. A case at Soroti central police station - Isamat Peace Adong (Uganda Christian University, 2024)
This research report was undertaken to examine the barriers and enablers of indigenous child protection. a case study at Soroti central police station under the child and family protection unit. It was guided by three objectives; to find out the socio-economic enablers of indigenous child protection, to examine the role of indigenous cultural practices in promoting child protection, to identify the barriers of accessing child protection services. The researcher used a sample size of 45 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective showed that socio-economic enablers has a significant effect on indigenous child protection. Supported by the following responses; 80% were positive to the statement that indigenous communities often face economic disadvantages, leading to higher vulnerability for children. Creating economic opportunities and promoting financial stability within indigenous communities can significantly contribute to child protection; 66.6% who were also the majority were positive to the statement that indigenous children's protection requires culturally sensitive services and support systems that respect and acknowledge their unique identities, languages, and cultural practices. Results of the second objective revealed that indigenous cultural practices has a significant effect on promoting child protection. Supported by the following responses; 64.5% were positive to the statement that indigenous practices focus on the intergenerational transmission of values, teaching children about respect, responsibility, and accountability. Results of the third objective showed that barriers have a significant effect on accessing child protection services. 73.4% forming the majority were positive to the statement that families may fear the negative judgment and societal repercussions that can come with accessing child protection services. There is need to promote community-based interventions that build on traditional practices, while incorporating modern child protection frameworks. Strengthening local economies through income-generating activities, access to education and healthcare can empower families to better protect children.K